Pengaruh Penggunaan Media ATM (Anatomi Tubuh Manusia) Terhadap Pemahaman Konsep Rangka Tubuh Manusia Pada Peserta Didik Kelas VI Sekolah Dasar - Salsabila Arrauyani; Wati Sukmawati (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of the use of HBA (Human Body Anatomy) media on the understanding of the concept of the human body skeleton in grade VI elementary school students. HBA media was developed as an interactive and visual learning tool to make it easier for students to understand the structure and function of the human body skeleton in a more real and interesting way. The research method used is quasi-experimental with a pretest-posttest control group design. Data was collected through concept comprehension tests before and after learning using HBA media. The test instrument used consists of 20 multiple-choice questions, where each question provides several answer options and participants are asked to choose one correct answer. The number of questions is designed to effectively and efficiently measure students' understanding in the context of learning or research, which are then analyzed using the Rasch model through WINSTEPS software. The research results showed a significant increase in the understanding of the human body skeleton concept in the experimental group analyzed with the Rasch model, compared to the control group using conventional learning methods. HBA media has been proven to be effective in increasing students' motivation to learn and understanding of human body skeletal materials. Thus, the use of HBA media can be used as an effective alternative learning media for human body skeletal materials in elementary schools.